Cannabidiol, ∆9-tetrahydrocannabinol, and metabolites in human blood by volumetric absorptive microsampling and LC-MS/MS following controlled administration in epilepsy patients - Pigliasco, Federica; Malaca, Sara; Lo Faro, Alfredo Fabrizio; Tini, Anastasio; Cangemi, Giuliana; Cafaro, Alessia; Barco, Sebastiano; Riva, Antonella; Pisati, Angelica; Amadori, Elisabetta; Striano, Pasquale; Tagliabracci, Adriano; et al. (Frontiers in Pharmacology, 2022)
Cannabidiol (CBD) exhibits anti-inflammatory, anxiolytic, antiseizure, and neuroprotective proprieties without addic-tive or psychotropic side effects, as opposed to Δ9-tetrahydrocannabinol (THC). While recreational cannabis contains higher THC and lower CBD concentrations, medical cannabis contains THC and CBD in different ratios, along with minor phytocannabinoids, terpenes, flavonoids and other chemicals. A volumetric absorptive microsampling (VAMS) method combined with ultra-high-performance liquid chromatography coupled with mass spectrometry in tandem for quantification of CBD, THC and their respective metabolites: cannabidiol-7-oic acid (7-COOH-CBD); 7-hydroxy-cannabidiol (7-OH-CBD); 6-alpha-hydroxy-cannabidiol (6-α-OH-CBD); and 6-beta-hydroxycannabidiol (6-β-OH-CBD); 11- Hydroxy-Δ9-tetrahydrocannabinol (11-OH-THC) and 11-Nor-9-carboxy-Δ9-tetrahydrocannabinol (THCCOOH). After overnight enzymatic glucuronide hydrolysis at 37°C, samples underwent acidic along with basic liquid-liquid extraction with hexane: ethyl acetate (9:1, v/v). Chromatographic separation was carried out on a C18 col-umn, with the mass spectrometer operated in multiple reaction monitoring mode and negative electrospray ionization. Seven patients with intractable epilepsy were dosed with various CBD-containing formulations and blood collected just before their daily morning administration. The method was validated following international guidelines in toxicology. Linear ranges were (ng/mL) 0.5-25 THC, 11-OH-THC, THCCOOH, 6-α-OH-CBD and 6-β-OH-CBD; 10-500 CBD and 7-OH-CBD; and 20-5000 7-COOH-CBD. 7-COOH-CBD was present in the highest concentrations, followed by 7-OH-CBD and CBD. This analytical method is useful for investigating CBD, THC and their major metabolites in epilepsy patients treated with CBD preparations employing a minimally invasive microsampling technique requiring only 30 µL blood.